Comparing digital detection platforms in high sensitivity immune‐phenotyping of extracellular vesicles. Issue 8 (3rd August 2022) - Frigerio, Roberto; Musicò, Angelo; Strada, Alessandro; Bergamaschi, Greta; Panella, Stefano; Grange, Cristina; Marelli, Marcello; Ferretti, Anna M.; Andriolo, Gabriella; Bussolati, Benedetta; Barile, Lucio; Chiari, Marcella; et al.
Abstract: Despite their clinical potential, Extracellular Vesicles (EVs) struggle to take the scene as a preeminent source of biomarkers in liquid biopsy. Limitations in the use of EVs origin from their inherent complexity and heterogeneity and from the sensitivity demand in detecting low to very low abundant disease‐specific sub‐populations. Such need can be met by digital detection, namely capable to reach the single‐molecule sensitivity. Here we set to compare, side by side, two digital detection platforms that have recently gained increasing importance in the field of EVs. The platforms, both commercially available, are based on the principles of the Single Particle Interferometric Reflectance Imaging Sensing (SP‐IRIS) and the Single Molecule Array technology (SiMoA) respectively. Sensitivity in immune‐phenotyping of a well characterized EV sample is reported, discussing possible applicative implications and rationales for alternative or complementary use of the two platforms in biomarker discovery or validation.